2017
DOI: 10.3390/en10101607
|View full text |Cite
|
Sign up to set email alerts
|

Power Controllable LED System with Increased Energy Efficiency Using Multi-Sensors for Plant Cultivation

Abstract: Abstract:In this paper, a power-controllable light emitting diode (LED) control system is proposed for plant cultivation. The proposed LED system measures environmental data, such as the distance between the plant and LED system using an infrared sensor and the ambient illuminance based on an illuminance sensor. Then, it converts the illuminance to the photosynthetic photon flux density (PPFD) for plant cultivation. It analyzes the relationship between the data and LED PPFD, and generates an optimal pulse widt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…One of the properties of solid state lighting is its fast switching speed and with a pulse width modulation LED driving circuit, the light output can be altered to be pulsing at a particular frequency and duty cycle. Studies have shown that it is possible to save on energy consumption by introducing pulsed LED outputs without having any effect on plant health. , Table summarizes some of the latest products or technologies related to grow lights. With much room for improvements to be made with regard to reaching the theoretical limit of the efficacy of LEDs, it can be said that the outlook for LEDs as artificial agricultural lighting looks promising, so long as the products can be made to be cost-effective.…”
Section: Grow Lightsmentioning
confidence: 99%
“…One of the properties of solid state lighting is its fast switching speed and with a pulse width modulation LED driving circuit, the light output can be altered to be pulsing at a particular frequency and duty cycle. Studies have shown that it is possible to save on energy consumption by introducing pulsed LED outputs without having any effect on plant health. , Table summarizes some of the latest products or technologies related to grow lights. With much room for improvements to be made with regard to reaching the theoretical limit of the efficacy of LEDs, it can be said that the outlook for LEDs as artificial agricultural lighting looks promising, so long as the products can be made to be cost-effective.…”
Section: Grow Lightsmentioning
confidence: 99%
“…Solutions that attempt to effectively match the light and dark phases of photosynthesis seem to be particularly promising. A key research challenge here is implementation of the high-precision pulse sequences necessary to optimise yield and energy savings [74].…”
Section: Light-emitting Diode Developmentmentioning
confidence: 99%
“…The main approaches to the development and design of modern systems of local and remote monitoring of parameters of agricultural and technical facilities by means of modern sensor and microprocessor technologies using current research methods are presented in (Vu, 2011;Ahn et al, 2017;Changizian et al, 2017;Pash et al, 2017;Shirsath et al, 2017;Zade et al, 2017;Drapaca, 2018). For example, modern approaches to biological object modeling, such as mathematical modeling of engineering systems, in view of various destabilizing effects are presented in the paper (Drapaca, 2018); the main approaches to the environmental factors which are distributed in space and time, and affect the quality of technical systems are presented in the paper (Pash et al, 2017); the study (Changizian et al, 2017) focuses on the results of research on ensuring effective control of photoelectric signals in technical objects.…”
Section: Current Research Findingsmentioning
confidence: 99%